2008
DOI: 10.1210/jc.2007-2430
|View full text |Cite
|
Sign up to set email alerts
|

Antiandrogens for the Treatment of Hirsutism: A Systematic Review and Metaanalyses of Randomized Controlled Trials

Abstract: Weak evidence suggests antiandrogens are mildly effective agents for the treatment of hirsutism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0
15

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(92 citation statements)
references
References 31 publications
1
76
0
15
Order By: Relevance
“…A systematic review and meta-analysis of randomized controlled trials assessing the efficacy of different antiandrogens for the treatment of hirsutism reported that when compared with metformin, flutamide reduced the hirsutism score by 5 (95% CI 3.0-7.0; I² = 0%). Spironolactone reduced the score by 1.3 (95% CI 0.03-2.6) [32]. Due to its propensity for severe hepatotoxicity, which is occasionally fatal, flutamide should not be used as first-line therapy for hirsutism.…”
Section: Flutamide and Bicalutamidementioning
confidence: 99%
“…A systematic review and meta-analysis of randomized controlled trials assessing the efficacy of different antiandrogens for the treatment of hirsutism reported that when compared with metformin, flutamide reduced the hirsutism score by 5 (95% CI 3.0-7.0; I² = 0%). Spironolactone reduced the score by 1.3 (95% CI 0.03-2.6) [32]. Due to its propensity for severe hepatotoxicity, which is occasionally fatal, flutamide should not be used as first-line therapy for hirsutism.…”
Section: Flutamide and Bicalutamidementioning
confidence: 99%
“…A CPA javasolt adagja hirsutismusnál 50-100 mg a ciklus 10. napján. Ugyanakkor a CPA alkalmazása hasonlóan eredményes lehet alacsonyabb dózisban (5-10 mg) is [41,42].…”
Section: Az Antiandrogének Alkalmazásaunclassified
“…Napi 5 mg fi nasterid eredményessége megegyezik az EE+CPA terápia eredményességével [47]. Dupla vak randomizált vizsgálat szerint a spironolacton hatásossá-gát a fl utamiddal és a fi nasteriddel megegyezőnek talál-ták [42]. A spironolacton vagy a fi nasterid OCP-vel tör-ténő kombinációja esetén az OR: 1,7 (95% CI 0,1-3,3), a fl utamid+MET kombinációjakor az OR: 4,6 [95% CI: 1,3-7,9], amely kedvezőbb, mint az OCP-vagy a METmonoterápia.…”
Section: Spironolacton Fi Nasterid Fl Utamidunclassified
See 1 more Smart Citation
“…La pérdida de peso es necesaria en las pacientes con sobrepeso. Además, se debe recurrir a tratamiento estético, que en el caso de las adolescentes mayores sería la fotodepilación-láser que parece ser más eficiente que la electrolisis 15,16 .…”
Section: Enfoque Diagnóstico Y Pruebas Complementariasunclassified